2021
DOI: 10.1016/j.nepr.2021.103228
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental health problems and sleep disturbances in nursing students during the COVID-19 pandemic: A systematic review and meta-analysis

Abstract: To identify the prevalence of mental health problems and sleep disturbances among nursing students during the COVID-19 pandemic. Background: As a future professional workforce, nursing students are expected to play a role in controlling the COVID-19 pandemic; however, physical and mental health problems may hinder their willingness to stay in the nursing profession. Evidence of the prevalence of the health problems among nursing students related to COVID-19 may allow educators to manage their students' health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
68
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 84 publications
10
68
2
5
Order By: Relevance
“…However, research has revealed that nursing students tend to have poor sleep quality [ 1 ]. A previous systematic review [ 2 ] of 17 studies involving 13,247 nursing students found that the prevalence of sleep disorders among nursing students during the COVID-19 pandemic ranged from 4.4 to 52.71%, with a prevalence of sleep disorders among nursing students in India of 4.4% [ 3 ], in Turkey of 28.26% [ 4 ], in the United States of 32% [ 5 ], and in Nepal of 52.71% [ 6 ]. Poor sleep quality directly affects nursing students’ physical health [ 7 ] in a manner similar to unhealthy habits like skipping breakfast or eating late-night snacks [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, research has revealed that nursing students tend to have poor sleep quality [ 1 ]. A previous systematic review [ 2 ] of 17 studies involving 13,247 nursing students found that the prevalence of sleep disorders among nursing students during the COVID-19 pandemic ranged from 4.4 to 52.71%, with a prevalence of sleep disorders among nursing students in India of 4.4% [ 3 ], in Turkey of 28.26% [ 4 ], in the United States of 32% [ 5 ], and in Nepal of 52.71% [ 6 ]. Poor sleep quality directly affects nursing students’ physical health [ 7 ] in a manner similar to unhealthy habits like skipping breakfast or eating late-night snacks [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this issue was highlighted in a systematic review that explored the prevalence of mental health problems and sleep disturbance among nursing students during the pandemic 3. The review suggested that over a quarter of respondents were experiencing sleep disturbances, nearly one-third were feeling stress or anxiety, and more than half reported suffering from depression.…”
mentioning
confidence: 99%
“…The importance of this issue was highlighted in a systematic review that explored the prevalence of mental health problems and sleep disturbance among nursing students during the pandemic. 3 The review suggested that over a quarter of respondents were experiencing sleep disturbances, nearly one-third were feeling stress or anxiety, and more than half reported suffering from depression. This review, and others, have highlighted -the substantial impact that the pandemic has had on nursing students, but what does the evidence tell us about why this group has been hit so hard?…”
mentioning
confidence: 99%
“…In a scenario of unpredictability and uncertainty, isolation exposes the population to stressful situations, rift in social ties, loss of job and income, withdrawal from in person educational and work activities (15) in view of the elevated risk of virus transmission and illness. Other studies showed symptoms of positive depression among students (9,16) and professionals (17) , so that the rates of depression onset tripled (from 8.5% to 27.8%) during the pandemic among the US population (6) . We found that the increase in vulnerability to mental disorders, directly or indirectly potentiated by the pandemic, has affected a substantial number of people from different social strata and regions of the country, showing the need for emergent interventions within the mental health field.…”
Section: Discussionmentioning
confidence: 96%